The contribution of functional morphologists to the development of medicine (the end of the XIX – the beginning of the XX centuries) - Deforzh, H. V. (History of science and technology, 2018)
Historical and scientific analysis of evolutionary morphology is extremely important for modern problems understanding of its development. The study of the morphology of animals is one of the bases of all studies of macroevolution and phylogeny, and consequently of general constructions in evolutionary theory as a whole. Thus, the study of the history of evolutionary morphology should be an essential element of the general history of evolutionary theory and an important point in covering general evolutionary problems. Evolutionary morphology has been experiencing its revival in recent decades. It is associated with the growing interest of biologists and physicians in the evolution of morphogenesis, structural transformations in the course of phylogenesis of various groups of organisms (especially humans) and their species-specificity.